The (Un) Constitutionality of The Citation for The Right Time in Brazilian Penal Code - Oliveira, Marcelo Queiroz Alves De (2015)
The citation for the right time in the criminal process, introduced by Law No. 11,719 / 2008 is a citation procedure to be used when there is suspicion that the defendant hide not to be named. This procedure allows the criminal trial of the accused without his having been personally cited. Thus, if the quote held by such means, the process will have its full development even if the accused is not aware of it. As a result, it has become an infringement on the exercise of their rights constitutionally guaranteed by the principles of legal defense and the adversarial, procedural guide for the technique, and also the American Convention on Human Rights. Therefore, this article intends to discuss the (un) constitutionality of that form of quotation regarding a possible violation of those principles. The methodology used for the construction of this article is to literature qualitatively through content analysis of theoretical basis of work in order to obtain material for research and solution of the proposed problem.